Developing A Self-Regulated Learning Guide For English Students - Yurni Yurni; Novita Triana (Universitas Batanghari Jambi, 2026)
This study aims to develop and evaluate a Self-Regulated Learning (SRL) Guide tailored for English Education students. Employing a Research and Development (R&D) design adapted from Borg and Gall, the study consisted of needs analysis, product design, expert validation, field testing, and dissemination. The needs analysis revealed that students experienced difficulties in goal-setting, time management, and self-reflection, indicating the necessity of structured SRL guidance. Based on these findings, an SRL Guide was developed integrating metacognitive, motivational, and behavioral strategies within English learning contexts. The prototype was validated by experts and achieved high validity scores (mean > 4.5). Field testing using a quasi-experimental design showed significant improvement in students’ SRL skills (p < 0.05), particularly in planning, monitoring, and reflection. Dissemination results indicated high acceptance among lecturers and students. The study concludes that the SRL Guide is valid, practical, and effective in enhancing learner autonomy and academic performance.